Sliding Mode Control of Ball Screw Meta-Action Unit Based on Disturbance Compensation and Inertia Identification - Ge, Hongyu; Wang, Cangfu; Zhang, Chuanwei; Yang, Manzhi (Shock and Vibration, 2023)
To solve the problems of dynamic model parameter perturbation and external disturbances during the operation of the ball screw meta-action unit, an adaptive sliding mode control method based on disturbance compensation and inertia identification is proposed in this paper. First, a model of the ball screw meta-action unit is established and the dynamic equation is derived. Taking into account the uncertainty of the dynamic parameters, a least squares method with a forgetting factor is introduced to identify the moment of inertia in real time, and the identification results are utilized to adaptively adjust the sliding mode control law. Second, a nonlinear disturbance observer is designed to effectively observe the load disturbance, and the observed value is substituted into the sliding mode control as feedforward compensation to improve the anti-interference ability of the controller. Committed to the chattering of traditional sliding mode control, an improved adaptive exponential sliding mode reaching law is exploited to construct a novel sliding mode controller, thereby suppressing the slid mode chattering more thoroughly. Finally, the superiority of the proposed method is verified by MATLAB/Simulink simulation and compared with the other two control methods; the control method proposed in this paper can effectively improve the tracking performance of the system and has good robustness.